Crystal Structure and Thermal Behavior of Two New Supramolecular Complexes Templated with 1, 2, 4, 5-Benzenetetracarboxylic Acid. (21st May 2012) - Gao, Ling-Ling; Liu, Yan; Lv, Xu-Yan; Liu, Jian-Feng; Hu, Tuo-Ping
Abstract : Templated coordination polymers [Ni(H2 O)4 (bipy)](BTA)0.5 · H2 O(1) and [Co(H2 O)4 (bipy)](BTA)0.5 · H2 O(2) (bipy = 4, 4′-Bipyridine, H4 BTA = 1, 2, 4, 5-Benzenetetracarboxylic Acid) were synthesized and characterized by single-crystal X-ray diffraction, powder diffraction, elemental analysis, IR, and thermogravimetric analysis. Both of complexes1 and2 are monoclinic crystal system, C2/c space group, and isostructural. The unit of the structure, the metal ion is coordinated by four water molecules and two bipy molecules, is a slightly distorted octahedral configuration, and the carboxyl group from BTA 4- ion doesn't coordinate with the metal ion, the H-bonding interactions further connect the mononuclear molecules to generate a 3D supramolecular complex.